MicroRNA-133a and Myocardial Infarction - Yi Xiao; Jiling Zhao; Julian P. Tuazon; Cesar V. Borlongan; Guolong Yu (Cell Transplantation, 2019)
Myocardial infarction (MI) is the leading cause of morbidity and mortality in the world. The infarcted heart displays typical cell death cascades characterized by a loss of cells and fibrotic scarring in the myocardium. Cardiac hypertrophy and fibrosis largely contribute to ventricular wall thickening and stiffening, altogether defining an adverse cardiac remodeling that ultimately leads to impaired cardiac function and subsequent heart failure. Finding a strategy to promote therapeutic, instead of detrimental, cardiac remodeling may pose as a potent MI treatment. Accumulating evidence shows that microRNAs (miRNAs) may play an essential role in cardiovascular diseases. In particular, microRNA-133a (miR-133a) is one of the most abundant miRNAs in the heart. Multiple studies have demonstrated that miR-133a participates in the early pathology of MI, as well as in subsequent cardiac remodeling. In this review, we summarize recent research progress highlighting the regulatory effects of miR-133a in ischemic myocardial diseases, such as inhibiting angiogenesis, apoptosis, fibrosis, hypertrophy, and inflammation, while promoting therapeutic cardiac remodeling. The goal is to elicit a critical discussion on the translational direction of miRNA-mediated treatments towards a safe and effective MI therapy.